Fabrication of rGO@MnSiO3 sandwich-like structure boosts the electrochemical properties of MnSiO3 for high-performance energy storage devices. (December 2021) - Dong, X.; Zhang, Y.; Jing, X.; Wang, Y.; Chen, X.; Hu, T.; Meng, C.
Abstract: Recently, emerging researchers suggest that manganese silicate (MnSiO3 ) has immense potential as electrode for supercapacitors (SCs). However, MnSiO3 's electrochemical performances in the reported literature are achieved far from desirableness owing to its poor electrochemical conductivity. Herein, we develop the honeymelon striated MnSiO3 coated on rGO sandwich-like structure (rGO@MnSiO3 ) to improve the energy-storing capabilities of MnSiO3 . The rGO@MnSiO3 is fabricated using the rGO@SiO2 templates by a facile hydrothermal procedure. The rGO@MnSiO3 is composed of rGO conductive inner core and MnSiO3 outer layer with the honeymelon-like shape. This integrated structure avoids the inactive electronic conducting trouble caused by the conventional MnSiO3 and rGO two-phase mixture system. At 0.5 A/g, the rGO@MnSiO3 electrode shows the specific capacitance of 576 F/g, which goes beyond rGO + MnSiO3 of 70 F/g, MnSiO3 of 90 F/g, and rGO of 70 F/g. At 1 mA/cm 2, the rGO@MnSiO3 symmetrical SC (rGO@MnSiO3 SSC) device shows the capacitances of 565 mF/cm 2 and illuminates the LED lamp for 3 min. This work not only demonstrates that the rGO@MnSiO3 sandwich-like structure can significantly promote the energy-storing capabilities of MnSiO3 but also provides a strategy for the synthesis of the homogeneous rGO@transition metal silicates construction that is beneficial to the electron and mass transfer in kinetics for energy storage and conversion. Graphical abstract: Image 1 Highlights: The core-shell structure with honeymelon striated rGO@MnSiO3 construction was prepared. The rGO in the rGO@MnSiO3 can significantly improve the conductivity of MnSiO3 . rGO@MnSiO3 achieves the specific capacitance of 576 F/g at 0.5 A/g. The capacitance retention of rGO@MnSiO3 is 84% after 6000 cycles. The rGO@MnSiO3 SSC device delivers the areal capacitances of 565 mF/cm 2 .